A compressed sensing faraday depth reconstruction framework for the MeerKAT MIGHTEE-POL Survey - Cárcamo, M; Scaife, A; Taylor, R; Jarvis, M; Bowles, M; Sekhar, S; Heino, L; Stil, J (IEEE, 2022)
In this work we present a novel compute framework for reconstructing Faraday depth signals from noisy and incomplete spectro-polarimetric radio datasets. This framework is based on a compressed-sensing approach that addresses a number of outstanding issues in Faraday depth reconstruction in a systematic and scaleable manner. We apply this framework to early-release data from the MeerKAT MIGHTEE polarisation survey.